Perfectionism and Procrastination among Gifted and Normal students at the College of Basic Education in the State of Kuwait - Alenezi, Salamah Ajaj (Journal of Educational and Psychological Sciences, 2022)
This study explores the relationship between Perfectionism and Procrastination, as well as identifying the differences between gifted and normal students in the College of Basic Education in Kuwait, and identifying the differences based on gender among gifted students. The study adopted the descriptive method. The study was implemented in first semester 2021-2022. The study sample including (1242) students; among which (720) gifted students in the College of Basic Education in the State of Kuwait.The study used two tools The Frost Multidimensional Perfectionism Scale and Arabic scale of Procrastination (ASP). The study results showed that, there were no differences between gifted and normal students in three dimensions of perfectionism (Concern over Mistakes - organization - personal standards) and the total score, while there were differences in the dimension of (Parental Expectations and Criticism) in favor of normal students, as well as differences in the procrastination in favor of normal students.The results of the study also found that there were no differences between the sample of gifted students (males and females) in two dimensions of perfection (Parental Expectations and Criticism - organization) and total score, while there were differences in two dimensions (Concern over Mistakes - personal standards) in favor of gifted males, as well as differences between gifted students (males and females) in the procrastination in favor of gifted male students.Also, the results showed that there is a positive correlation between three dimensions of perfectionism and procrastination among the sample of gifted students, while a negative correlation was found in the third dimension in the perfectionism (organization) and procrastination. The study recommended the necessity of paying attention to talented students and establishing a special committee for them within the college to deal with them and help them overcome the difficulties they face.
Keywords: Perfectionism; Procrastination; Gifted